Sourire en crise. Les photoreporters de l’Albanie communiste (1944-1991) - Gilles de Rapper (El Argonauta Español)
This study focuses on photojournalists as a distinct category of photographers. Consequently, the background of this article is not the history of journalism and journalists, but the history of photography as it can be reconstructed in the particular context of socialist Albania (1944-1991). The dictatorship established by Enver Hoxha in 1944 and which survived until 1991 produced an immense quantity of photographs that cannot be reduced to the category of "propaganda photography" generally associated with the photographic production of totalitarian regimes. Because of their number, distribution and political constraints, press photographs constitute a particularly important genre of this production, and it is with them, or more precisely with their producers, that the study deals. The aim of this article is thus to grasp the meaning of the category of "photojournalist" and to explain its characteristics and transformations throughout the socialist period in Albania.